Quality of Multiple Choice Questions (MCQs) as perceived by the postgraduate residents appearing in Mid Training Assessment (MTA) during January 2022 at Rawalpindi Medical University: Quality of Multiple-Choice Questions (MCQs) as perceived by the postgraduate residents appearing in Mid Training Assessment (MTA) - Shahid, Rizwana; Asad, Muhammad; Khalid, Rabbia (Pakistan Journal of Health Sciences, 2022)
Impartiality and reliability of Multiple-Choice Questions (MCQs) render them an ideal assessment tool for measuring higher order cognition. Objective: To determine the perception of postgraduate medical trainees pertinent to the quality of MCQs administered in Mid Training Assessment (MTA) January 2022. Methods: A cross-sectional descriptive study was carried out among 40 postgraduate trainees who appeared in MTA during January 2022. About 23, 12 and 05 of these trainees were doing MS and MD training at Benazir Bhutto Hospital, Holy Family Hospital and DHQ Hospital Rawalpindi respectively. Trainees were enrolled in the study through consecutive non-probability sampling. The feedback from the trainees about quality of MCQs was gathered by means of a structured questionnaire based on 5-point likert scale. Data analysis was done by using SPSS version 25.0. Results: About 67% of the trainees were pleased with the quality and construct of MCQ in their assessment in terms of illustration of the information in their stems needed to understand the clinical problem. More than 82% trainees satisfied with the time allocated for attempting MCQs papers. Only 55% trainees agreed with alignment of MCQs with given Table of Specification (TOS). Most (32.5%) wanted to have difficulty level of the MCQs in accordance with level of training. Around 27.5% and 22.5% of the residents proposed to incorporate more clinical reasoning and problem solving MCQs respectively. Conclusions: Trainees were substantially contented with the standard of MCQs. They suggested for inclusion of more clinical reasoning and problem-solving type questions in alignment with TOS.